Exercise and Sports Science Australia (ESSA) position statement on exercise for people with mild to moderate multiple sclerosis - Hoang, Phu D. (2024)
Objectives: Multiple sclerosis (MS), the most common chronic and progressive neurological condition of the central nervous system, affects 26,000 Australian adults. Exercise training has beneﬁcial effects on MS-related impairments including reduced muscular strength, poor aerobic capacity and impaired mobility, and in consequence can improve quality of life. This Position Statement provides evidence-based recommendations for exercise prescription and delivery of exercise training for people with MS with mild to moderate disability. Design and methods: Synthesis of published works within the ﬁeld of exercise training in MS. Results: Exercise provides many beneﬁts to people with MS. There is strong evidence that resistance and aerobic training, performed 2 to 3 times per week at a moderate intensity, are safe and can improve muscle strength, car- diorespiratory ﬁtness, balance, fatigue, functional capacity, mobility and quality of life in people with MS with mild to moderate disability (Expanded Disease Severity Scale (EDSS) ≤ 6.5). However, the evidence for those with severe disability (EDSS >6.5) is less clear. The effects of exercise on MS pathogenesis, central nervous structures and other outcomes such as depression and cognitive impairment, have not been adequately investigated. Effective exercise interventions to improve balance, joint contractures and reduce falls in people with MS are also urgently needed as well as investigations of long-term (≥1 year) effects of exercise training. Conclusions: Resistance and aerobic training exercises are effective to alleviate some characteristic signs and symptoms in MS and should be supplemented by balance exercise to prevent falls. Exercise training programs should be prescribed and delivered by qualiﬁed exercise professionals. It is important to recognise and accommo- date exercise-associated complications such as fatigue and heat sensitivity.